2004
DOI: 10.1111/j.0092-5853.2004.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Entering the Arena? Gender and the Decision to Run for Office

Abstract: A critical void in the research on women's underrepresentation in elective office is an analysis of the initial decision to run for office. Based on data from our Citizen Political Ambition Study, the first large-scale national survey of potential candidates, we examine the process by which women and men emerge as candidates for public office. We find that women who share the same personal characteristics and professional credentials as men express significantly lower levels of political ambition to hold elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
243
2
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(267 citation statements)
references
References 34 publications
8
243
2
14
Order By: Relevance
“…Women are more than 40% more likely than men to retire when their ability to influence the legislative process stalls. Coupled with recent studies that conclude that women are less likely than men to seek public office (Fox and Lawless 2004), our results indicate that prospects for women's representation and gender parity are less promising than the conventional wisdom suggests.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Women are more than 40% more likely than men to retire when their ability to influence the legislative process stalls. Coupled with recent studies that conclude that women are less likely than men to seek public office (Fox and Lawless 2004), our results indicate that prospects for women's representation and gender parity are less promising than the conventional wisdom suggests.…”
supporting
confidence: 76%
“…Two recent studies call these assumptions into question. First, potential women candidates remain less likely than similarly situated men to receive encouragement to run for office and to deem themselves qualified to hold elected positions, both of which decrease their likelihood of throwing their hats into the electoral arena (Fox and Lawless 2004). Second, this article argues that even when women make it to the House, they serve significantly shorter terms than men do, in large part because women are more likely to retire as a consequence of facing a career ceiling.…”
Section: Resultsmentioning
confidence: 93%
“…While we have pulled from a variety of quantitative and qualitative work in contextualizing our findings, as well as rigorous methods to explore the questions raised, further research with more fine-grained measures and a longitudinal component would be helpful. As more women take highly visible political roles, as has been the trend in recent years, women’s political efficacy and interest will catch up to men’s and this relationship may strengthen and increase women’s participation (Atkeson 2003; Atkeson and Rapoport 2003; Fox and Lawless 2004). Examining these relationships over a longer period of time would help address such questions.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have found that women are less likely than men to run for political office [23,24] and this results in a limited number of viable female candidates that voters can choose from. In their comprehensive analyses of the political ambition of women, Fox and Lawless [6,7] found that even when women have the same personal characteristics and qualifications as men, the women are less likely to seek elective office. This is due to several factors including the lack of encouragement by political and non-political actors to run for office.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, even when women have the qualifications to run for political office, research tells us that there is a gender gap in political ambition. Fox and Lawless [6,7] conclude that women are more likely than men to question their credentials when determining whether to run for political office. In other words, despite women and men's similar personal and professional characteristics, women have lower levels of political ambition than men do.…”
Section: Introductionmentioning
confidence: 99%